MENGUJI STRUKTUR MODAL, UKURAN PERUSAHAAN DAN TATA KELOLA PERUSAHAAN TERHADAP PROFITABILITAS (Studi Empiris Pada Sub Sektor Perusahaan Makanan Dan Minuman Yang Terdaftar Di BEI) - Havinda NurJannah; Nur Kholis (Journal of Innovation Research and Knowledge, 2024)
The focus of this research is to examine the influence of capital structure, company size and corporate governance on profitability through quantitative methods. The population used is food and beverage companies listed on the Indonesia Stock Exchange in 2017-2020. Capital Structure is measured through the Debt to Equity Ratio (DER) variable, company size is calculated through the market capitalization variable, Corporate Governance is calculated through the independent commissioner variable and profitability is measured using the Return on Assets (ROA) variable. The data in this research was obtained through the financial reports of the sample companies so it is classified as a type of secondary data. The population in this study was 29 companies. Sample selection was carried out using a purposive sampling method, the number of samples was 15 companies. The data analysis technique in this research uses multiple linear regression analysis. Based on the results of the hypothesis testing analysis, it can be concluded that capital structure has a significant positive effect on profitability, while the variables company size and corporate governance have an insignificant negative effect on profitability